Serum adiponectin among different stages of type 2 diabetes mellitus patients - Dr. Rashmi G S Basavaraj; Dr. Ravikumar Malladad (Tropical Journal of Pathology and Microbiology, 2021)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder that leads to micro and macrovascular complications. Nephropathy is the most common microvascular complication. For diagnosis of nephropathy in T2DM patients by using urinary albumin, this is not a sensitive and specific biomarker because it is elevated in other conditions. we aimed to evaluate the serum adiponectin for early detection of nephropathy in patients with type 2 diabetes mellitus.Methods: A total of 60 subjects were included in the present study and further subdivided into 30 patients T2DM with normoalbuminuria, 30 patients with microalbuminuria. All the patients were included after obtaining institutional ethical permission and consent forms. Blood and urine samples were collected from all the subjects and proceed with further analysis. Appropriate statistical analyses were used for different types of data analysis.Results: Increased levels of FBS, PPBS, HbA1C and serum adiponectin were observed in two groups of T2DM patients. Statistically elevated levels of serum Urea, Creatinine and Uric acid levels were observed in patients T2DM with microalbuminuria when compared to T2DM with normoalbuminuria. The serum adiponectin was positively correlated with FBS, PPBS, HbA1C, Urea, Creatinine, Uric Acid and Urinary Albumin in patients with two groups of T2DM.Conclusion: This study concluded that measuring the serum adiponectin levels may be useful for the early detection of nephropathy in patients with T2DM.